APLIKASI PENDAFTARAN SANTRI BARU RUMAH YATIM DAN QUR’AN MADANI BERBASIS WEBSITE: Studi Kasus pada Rumah Yatim dan Tahfidz Qur’an Madani Bandung - Ulul Fatha Lovakri; M. Syafiuddin Usman (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This report is a result of final project research that serves as one of the requirements for obtaining a bachelor's / diploma degree. This research took place over a period of 30 days and was carried out in a place that became the object of the research. The object of this research is aimed at an educational institution, namely the institution in question is Rumah Yatim and Tahfidzh Quran Madani Bandung. The problem that exists at the institution lies in the new student registration system which still uses a manual method in the registration process. The data from the registrants still uses archives from Google Form assistance which has not kept up with today's technological developments, one of which is in the use of website applications. Therefore, in this research, a simple website-based new student registration application will be made using the codeigniter framework which is expected after this research the application can be used to facilitate the Institute in the process of registering new students.